RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PEMESANAN FLORIST HARI MELATI BANGIL BERBASIS WEB DENGAN MODEL PROTOTYPE - Mochamad Andi Rahmansyah; Dwanoko, Yoyok Seby; Agustina, Rini (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2024)
The use of information technology in modern times like today is very much needed to support various activities, one form of information technology that is often used to support business operations is through the use of websites. Florist Hari Melati is a flower shop that has been established for decades, but this florist still uses a manual ordering system. The system that still uses this manual method causes various obstacles and problems for each user in the system. Based on these problems, a Florist Order Management Information System was formed with a prototype method that aims to assist in data management and order transactions. The results obtained from the User Acceptance Test showed that 91.13% of respondents agreed that this system could have a positive impact on florist management and could also support the ordering system at the Hari Melati Florist.